2023
DOI: 10.29333/ajqr/12950
|View full text |Cite
|
Sign up to set email alerts
|

Happiness in Parents of Children with Autism Spectrum Disorder: A Qualitative Study

Abstract: <i>Literature reports the challenges of parenting a child with Autism Spectrum Disorder (ASD), and its impacts on emotional and psychosocial wellbeing, both generally and specifically in the Hong Kong context. Positive parenting experiences are less well defined; however, research and theory in the positive psychology field suggests that people living with adversity can find and create meaning, positivity and happiness. This study aimed to investigate Hong Kong parents’ experiences and perceptions of hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…For example, parents might have different thoughts regarding the impact of having a child with ASD. Some parents might think that their child with ASD makes their life more meaningful and has brought them many unique pleasures (e.g., parents found new perspectives on life goals and happiness; Chau & Furness, 2023;Schlebusch & Dada, 2018;Schlebusch et al, 2016). This is an example of positive cognitive appraisal.…”
Section: Cognitive Appraisalmentioning
confidence: 99%
“…For example, parents might have different thoughts regarding the impact of having a child with ASD. Some parents might think that their child with ASD makes their life more meaningful and has brought them many unique pleasures (e.g., parents found new perspectives on life goals and happiness; Chau & Furness, 2023;Schlebusch & Dada, 2018;Schlebusch et al, 2016). This is an example of positive cognitive appraisal.…”
Section: Cognitive Appraisalmentioning
confidence: 99%
“…Parents of Autistic children have described the many benefits of raising an Autistic child including developing loving bonds with their child, personal growth, and new social opportunities (Chau & Furness, 2023; Meleady et al, 2020; Potter, 2016). Although parents of all children experience some challenges in raising their children, parents of Autistic children have additional challenges in supporting their child to thrive in a world that is not designed to meet their needs (Davy et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Co‐occurring conditions such as Intellectual Disability (ID) and Attention Deficit Hyperactivity Disorder (ADHD) are also commonly diagnosed in Autistic people (e.g., Matson & Shoemaker, 2009), which can add complexity for parents as they learn to support and parent their child. Several studies have found that parents of Autistic children associate their parenting role with many positive outcomes such as developing loving bonds with their child, experiencing personal growth, and encountering new social opportunities (Chau & Furness, 2023; Meleady et al, 2020; Potter, 2016). However, parents also recognize the increased challenges associated in providing support to help their child to thrive in a world that is mostly not suited to their needs (Davy et al, 2023; Safe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%